Recent advances in friction stir spot welding of aluminium and magnesium alloys: Techniques, challenges, and future trends - Muhammad Irfan Naim, Abd Rahim; Nur Syafiqah, Nor Sofian; Juliana, Jumadi; Luqman Hakim, Ahmad Shah; Quazi, M. M. (IOP Publishing Ltd, 2025)
Friction Stir Spot Welding (FSSW) is a solid-state joining technique that has seen growing use for aluminium and magnesium alloys due to its ability to minimize defects and enhance joint performance. This review highlights recent advancements in FSSW of both similar and dissimilar Al-Mg alloy systems, with a focus on microstructural evolution, mechanical behaviour, and welding process parameters. It also discusses innovative strategies, such as the use of interlayers, tool design modifications, and process variants, which address challenges like intermetallic formation and joint integrity. Furthermore, the paper explores computational modelling and emerging smart control systems for process optimization. This review highlights the comprehensive use of various key characterization techniques, ranging from microstructural analysis to advanced imaging methods, to evaluate FSSW joints. Finally, the review outlines current limitations and future research directions to guide both academic and industrial progress in lightweight alloy joining.